The Influence of External Locus of Control, Compensation Suitability, and Internal Control Effectiveness on Accounting Fraud Tendency - Andhini Puspita Ningrum; Rizal Yaya (IECON: International Economics and Business Conference, 2025)
The research is intended to examine the possibility that external locus of control, compensations suitability, and effectiveness of the internal control may contribute to person committing a crime of accounting fraud tendencies. The research object is the village government of Kulon Progo Regency, which is comprised of village governments of Pengasih, Kokap, Wates, Panjatan and Temon. The present study used sample of village government workers such as the Village Head (Lurah), Village Secretary (Carik), and Village Treasurer (Danarta) in 41 villages in the Kulonprogo Regency. In this study, a tool called SPSS will be applied. Findings of the analysis indicate that external locus of control has a considerable positive impact on the predisposition of accounting fraud. The appropriateness of compensation does not have any considerable impact on the propensity of the accounting fraud. And, lastly, the efficiency of internal control has an important adverse impact on the propensity towards accounting fraud.